Assessment of the utility of the National Health Service England Low Back and Radicular Pain Pathway: analysis of patient reported outcomes. Issue 1 (February 2020) - McKeag, Philip; Eames, Niall; Murphy, Lynn; McKenna, Raymond; Simpson, Eilish; Graham, Gillian
Introduction: Lumbar disc herniation causing radiculopathy is a common reason for referral to spinal out-patient clinics. At our centre following routine referral, patients wait a mean of 109 weeks for a consultation with a spinal surgeon. A pathway in keeping with the National Health Service England Low Back and Radicular Pain Pathway was introduced with two objectives. Patients would be seen sooner by suitably trained health care professionals to avoid long waiting times for assessment with a spinal surgeon, and if a set of criteria were met, they would receive a selective nerve root injection to manage their pain. Methods: Patients were seen by specially trained orthopaedic physiotherapists following routine general practitioner (GP) referral. A radiologically guided nerve root injection was carried out if patients had radicular pain between 6 and 52 weeks duration and a magnetic resonance imaging (MRI) scan demonstrating an intervertebral disc prolapse correlating with their radicular symptoms. Patient-recorded outcome measures were taken before and after nerve root injection. Results: Seventy five patients entered the pathway. Mean patient age was 49.9 years and 27 patients (36.0%) were male. Mean time from referral to assessment was 15.5 weeks. Mean visual analogue score (VAS) for leg pain was 7.4 out of 10 before nerve root injection and 4.8 out of 10 following nerve root injection (p < 0.001). Mean Oswestry Low Back Pain Disability Questionnaire score before nerve root injection was 58.4% and 49.7% following nerve root injection (p = 0.024). Mean Euroqol EQ-5D-5L Health Index was 0.2 before nerve root injection and 0.4 afterwards (p < 0.001). Conclusion: This study suggests that this pathway may help to reduce waiting times for patients with lumbar radiculopathy secondary to intervertebral disc prolapse. The resulting enhanced care may be associated with a reduction in leg and back pain and an improvement in quality of life.